Anxiety Survey in Football Athletes in Cases of Anterior Cruciate Ligament Injuries - Falah Nur Fajri; Ricky Wirasasmita; Sony Hasmarita (STKIP Pasundan Press, 2026)
This study aims to determine the level of anxiety in soccer athletes who experience Anterior Cruciate Ligament injuries. The formulation of the problem in this study is: How high is the level of anxiety in soccer athletes in cases of Anterior Cruciate Ligament injuries? The study used a descriptive method with a survey approach. The population in this study were 15 soccer athletes who were undergoing physiotherapy at Ibest Physio Bogor, with a total sampling technique, because the entire population had the same symptoms. The sample in this study were soccer athletes who were undergoing recovery at Ibest Physio Bogor, totaling 15 people from the entire population. The research instrument was a questionnaire consisting of 26 statement items with a rating scale of 1 to 5. Data processing used descriptive percentage analysis. The results showed that the maximum value obtained was 94, the minimum value was 78, the average was 85.47, the median was 3.29, and the standard deviation was 1.02. The final results showed that 13% of athletes experienced anxiety within reasonable limits and were still able to control their emotions even though they felt afraid and doubtful. As many as 86% of athletes showed high to very high anxiety. These findings prove that ACL injuries have a significant impact on the psychological condition of athletes. Therefore, attention and assistance from coaches, physiotherapists, and sports psychologists are needed so that recovery runs more optimally physically and mentally.